Unidad hospitalaria de atención integral e investigación oncológica: exploración de la salud por medio de la arquitectura sensorial y flexible y su adaptabilidad en el tiempo (2021)
Hospital architecture has the ability to act as a therapeutic means to promote an improvement in the treatment of hospital patients and in general to promote the welfare and tranquility of the users who visit these spaces, in which, one of the specialties of medicine in those that their patients travel and inhabit during much of the treatment in these hospital centers are cancer patients. The city of Armenia, in Colombia, has a deficit in oncology hospital facilities, due to the number of patients it receives at the departmental level, and the relationship between the number of reported cancer cases and the number of the department's population . A comprehensive care and cancer research center is proposed to function as a complement to the San Juan De Dios university hospital, being located in an adjacent lot.